Itajaí, Santa Catarina - Azorean ancestry and spinocerebellar ataxia type 3 Itajaí, Santa Catarina - Descendência açoriana e ataxia espinocerebelar tipo 3 - Teive H.A.G. (2016)
© 2016, Associacao Arquivos de Neuro-Psiquiatria. All rights reserved.The authors present a historical review of spinocerebellar ataxia type 3/Machado-Joseph disease (SCA3/MJD), the most common form of spinocerebellar ataxia in Brazil, and consider the high frequency of cases in families from Itajaí, a city on the coast of the state of Santa Catarina with a large population of Portuguese/Azorean descent.